Seismic vulnerability assessment using regional empirical data. - Yakut, Ahmet
This article presents a procedure developed for the seismic performance assessment of low- to mid-rise reinforced concrete buildings in Turkey. The past performance of reinforced concrete buildings during major earthquakes have been compiled and analysed comprehensively using statistical procedures in order to study the empirical correlation between the significant damage inducing parameters and the observed damage. A damage database of nearly 500 representative buildings experiencing the 1999 Kocaeli and Düzce earthquakes have been used and discriminant functions expressing damage score in terms of six damage inducing parameters have been developed. In order to extrapolate the procedure to other regions that are likely to be subjected to major earthquakes a new approach that takes into account different local soil conditions, site-to-source distance and the magnitude of the earthquake has been introduced. The procedure has been applied to a pilot area in Istanbul to estimate expected damage distribution under a credible scenario earthquake.
Keywords: Performance assessment; Seismic vulnerability; Reinforced concrete; Building safety